ORAL LITERATURE EXISTENCE IN MILLENNAL ERA: BETWEEN THE ENVIRONMENT AND RELIGION - Abdul Karim Wirawan (Jurusan Sastra Indonesia, 2019)
This paper attempts to describe the existence of oral literature in the millennial era. Oral literature in the millennial era must have an applied function. That is, oral literature does not stand alone, but rather has a role and contribute to the environment and surrounding communities. These contributions include aspects of religiosity and environmental aspects. From the aspect of religiosity, oral literature is a form of literature that contains the high religious value. This is mainly due to the influence of religions that have and have developed in the Java region. On the environmental aspect, oral literature has an important role in environmental preservation. Oral literature forms a taboo that develops in a society that indirectly impacts on the nature of nature.